Dissection of quantitative resistance to rice diseases - Manosalva, Patricia M. (Kansas State University, 2006)
Because it is predicted to be durable and broad spectrum, quantitative trait loci (QTL)-based resistance is an important option for rice disease control. However, manipulation of this type of resistance requires knowledge of the contributing genes. This study demonstrates the contribution of two of three defense response (DR) genes to QTL-governed resistance, and identifies a third gene that negatively regulates resistance. The contribution to QTL-governed resistance of one of nine rice OsPAL genes, which encode phenylalanine ammonia-lyase, was determined using reverse genetics. Mutant ospal4 contains a 750 bp deletion in OsPAL4 and was identified using a PCR-pooling strategy. OsPAL4 underlies a QTL on chromosome 2, and is located in cluster with three other OsPAL members. Rice lines mutated in OsPAL4 are more susceptible to a virulent strain of Xanthomonas oryzae pv. oryzae (Xoo) than lines with the wild type allele. RNAi suppression was used to evaluate the contributions of genes encoding oxalate oxidase-like proteins (OsOXL) and a 14-3-3 protein (GF14-e) to disease resistance. Silencing of 12 OsOXL genes clustered on chromosome 8, varied from suppression of a few gene members to silencing of all expressed family members. Screening of transgenic lines by challenge with Magnaporthe grisea (Mg), the rice blast pathogen, revealed that the more chromosome 8 OsOXL genes suppressed, the more susceptible the plants were to Mg. GF14-e co-localizes with a disease resistance QTL on chromosome 2. Specific suppression of GF14-e by RNAi silencing did not result in enhanced susceptibility to Mg. Instead, the lines exhibited spontaneous HR-type lesions. The presence of this lesion mimic phenotype correlated with enhanced resistance to a virulent strain of Xoo, suggesting that the GF14-e encoded 14-3-3 protein functions as a negative regulator of plant cell death and bacterial resistance in rice. This study supports the hypothesis that DR genes, such as OsOXL and OsPAL4 contribute to disease resistance governed by QTL. The role of GF14-e is less clear, however its down regulation may contribute to QTL-governed resistance. Thus, incorporation of regions harboring the effective DR gene alleles into rice will enhance broad spectrum and durable resistance.
Keywords: Quantitative resistance; Candidate genes; Rice; Agriculture, Plant Pathology (0480)